Analisis Bibliometrik Perubahan Perilaku Politik, Menggunakan Vosviwer - Abdillah, Ashar (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2023)
Bibliometric analysis is the mapping of research research trends by processing metadata from Google Scolar. The goal is to find out research trends on political behavior through searching the Google Scholar database with the keywords political behavior. Retrieval of metadata using the Publish or Perish application. The resulting data is then analyzed descriptively based on the year of publication publication, publisher name, researcher productivity, and journal ranking. For get an accurate research development map, PoP data is exported to the Excel CSV and Result as RIS file formats. CSV data is made into a pivot table and RIS data is analyzed using the VOSViewer (VV) application. The research results show that the number of research publications has increased in 2020-2022. In 2021, the number of publications was the highest, namely 46 articles, while in 2022 there were 33 articles, and in 2020 there were only 23 articles. The results of the analysis on the VOSViewer application show 4 clusters with 19 items in them. Cluster 1 (red) discusses Analysis, Indonesia, politics, study. Cluster 2 (green) on political behavior, case study. Cluster 3 (blue) includes research results that lead to politics. Cluster 4 (yellow) focuses on political trust through elections. Meanwhile the results of the analysis occupy a discussion on politics, political behavior, elections, studies in Indonesia which have a lot of research results while research that is not related to political beliefs and case studies related to politics